Influence of Al2O3nanoparticles' incorporation on the structure and electrical properties of Pb0.88Sr0.12Zr0.54Ti0.44Sb0.02O3ceramics - Pharatree Jaita (2018)
© 2016 Author(s). In this research, the effects of an Al2O3nanoparticle additive on the structure and electrical properties of Pb0.88Sr0.12Zr0.54Ti0.44Sb0.02O3(PSZST) ceramics were investigated. The PSZST ceramics with the addition of 0 - 2.0 vol % Al2O3were fabricated via a solid-state mixed oxide method and sintering at 1250°C for 2 h to obtain dense ceramics. X-ray diffraction indicated that all compositions exhibited a single perovskite structure. Phase identification showed coexisting mixed rhombohedral and tetragonal phases for the modified ceramics, while the unmodified ceramics showed a rhombohedral-rich phase. The addition of Al2O3nanoparticles was also found to improve the densification and the electrical properties of the PSZST ceramics, such as dielectric constant and polarization. The 2.0 vol% sample showed the highest low-field piezoelectric coefficient (d33) value of 646 pC/N, which was 90% higher than that of the unmodified sample, suggesting that this composition had the potential to be one of the promising piezoelectric ceramic candidates for further use in actual applications.